Border fetishisms material objects in unstable spaces - Spyer, Patricia 1957- (Zones of religion, 1998)
The essays here explore the varied nature of commodity fetishism in colonial & post-colonial spaces. Using case studies the contributors call for the inclusion of material things within the wider human experience.